Attitudes of social work students towards older people. Issue 5 (2nd September 2016) - Duyan, Gülsüm Çamur; Tuncay, Tarık; Özdemir, Burcu; Duyan, Veli
Abstract : Demographic ageing is a challenge for many countries. Even though Turkey has a relatively younger demographic composition, the proportion of the older people (65+) within the population is rapidly increasing. Within this framework, older people are becoming more important clients for both social work students and social workers in Turkey. This study aims to reveal the attitudes of social work students towards older people and determine the various factors that affect their views on older persons. In the scope of the project, Kogan's Attitude Towards Old People Scale was applied to 419 social work undergraduate students at a university located in Central Anatolia. The findings showed that social work students scored a mean of 130.96 and they generally had positive attitudes towards older people. The correlation between year of study, gender and age was not statistically significant. However, having lived mostly in urban areas was positively correlated with the mean Kogan scores and this finding was found to be statistically significant. Exposure to personal contact with older people at both the personal and professional levels was influential in shaping attitudes about the older people.